Influência do uso de laser na estimulação do reparo ósseo alveolar: revisão sistemática - Lemes, Carmen Helena Jacques (2015)
In dental literature the use of laser therapy is rich in information about the laser action in soft tissues, dental implants, bone cavities or injuries, except in the alveolar bone repair. The aim of the present study was to gather evidence, by means of a systematic review of the literature, to support or not the use of laser in the stimulation of alveolar bone repair after dental extraction. The methods were carried out according to the PRISMA guidelines. Bibliographic structured searches were carried out in databases: IBECS/Bireme, ISI Web of Science, LILACS/Bireme, MEDLINE/PubMed, SciELO, Scopus and The Cochrane Library using descriptors related to the topic. The eligibility criteria included: clinical studies or studies using animal model to compare the alveolar bone healing repair after dental extraction with and without the use of laser, with quantitative or qualitative analysis of alveolar bone repair as outcome. Only studies published in English, Spanish and Portuguese and published from 1995 to 2014 were selected. The last search was conducted in December 2014, in which 3235 records were found (551 duplicates), and 2684 were screened by titles and/or abstracts. Five articles were selected for full-text reading, and four were included in the review. Data were extracted and categorized according to the type of tooth extracted, type of laser used, power (mW), wavelength (nm), energy dose applied (J/cm2), time, distance, and application protocol, a postoperative period of observation. Although few studies have been included in this review, all of them using animal models, the literature suggests that the laser therapy might have a positive effect on acceleration of alveolar bone repair after tooth extraction. However, clinical studies are needed to assess more clearly the benefits of laser therapy after dental surgery, particularly regarding the type of laser, power, wavelength, energy dose and method of application.